Validating a Mobile Learning Readiness Survey: Assessing Teachers' Dispositions Toward Adoption. Issue 4 (2nd October 2017) - Christensen, Rhonda; Knezek, Gerald
Abstract: Appraisal of the readiness of teachers to accept and use mobile devices for classroom instruction is a critical step whenever an expectation exists that the devices will be used to enhance student learning. Designing professional development requires assessment of teachers' readiness and willingness to embrace mobile learning for their students. This article features a validation study of a survey instrument for assessing the level of readiness of classroom teachers for teaching and learning with mobile devices. Through exploratory factor analysis of the Mobile Learning Readiness Survey (MLRS), four dimensions of readiness to teach with mobile devices were identified. These four factors are possibilities, benefits, preference, and external influences. Multidimensional scaling was then applied to the scales produced from items associated with the factors, in order to examine the associations among the constructs. Findings demonstrate that the constructs measured by the MLRS align with other established measures that would be expected to have significant associations with the newly developed MLRS scales. The instrument is demonstrated to possess desirable psychometric properties of respectable reliability, plus acceptable content, construct, and criterion-related validity, making it worthy of use in technology integration research and professional development contexts.